Permasalahan Pergaulan di Sekolah Dasar (SD) - Eka Bagus Pramudya; Gracia Natalia Putri; Mella Tia Tristanti; Maharani Dwi Wahyu Nindiasari; Panji Adi Nugroho (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
Social problems in elementary schools are an important aspect in children's social development. However, social problems can arise and affect students' emotional well-being and academic achievement. This study aims to identify social problems that commonly occur in elementary schools and analyze their impact on students. This research method uses literature studies and case analysis to understand the dynamics of social problems in elementary schools. The results of the study indicate that social problems in elementary schools are often related to bullying, difficulty interacting with peers, and the influence of the school environment. The impact of these problems can be emotional stress, decreased academic achievement, and difficulty in building healthy social relationships. This study recommends the importance of early intervention and support from teachers and parents to overcome social problems in elementary schools and create a safe and supportive school environment. Thus, students can develop optimally and achieve their academic and social potential.